EXPLORING MISCONCEPTIONS ABOUT THE CHARACTERISTICS OF SOLID, LIQUID, AND GAS AMONG JUNIOR HIGH SCHOOL STUDENTS IN KAMPOT PROVINCE, CAMBODIA - Sreypouv, Ouch; Shimizu, Kinya (Unnes Science Education Journal, 2017)
Research shows that students’ misconceptions interfere with students’ learning of scientific concepts. Meanwhile, the significant effects of students’ misconceptions on their achievement has been a concern for teachers who strive to find ways of dealing with the misconceptions. This study was conducted to explore Cambodian students’ misconceptions of states of matter (Solid, liquid, and gas), which main aimed to investigate what type of misconceptions which they held in the concept of characteristics of solid, liquid, and gas. Data was collected using a 15 multiple-choice two-tier test which was administered on 330 junior high school students in Kampot province, Cambodia. In this test, students’ responses were categorized into three: correct answer, misconception, and incorrect answer. Data analysis through descriptive statistics showed the frequencies of each students’ misconceptions. Students’ responses to the items revealed that 20 misconceptions were held by less than 50% of the students whereas 4 misconceptions were held by more than 50% of the students who took the test. Interviews with some of the students revealed the nature of students’ understanding of the concept of states of matter. Two main conclusions were derived to explain these results: 1) students tend to attribute macroscopic view to microscopic view and 2) students believe matter exist unless they see.